Shifting modes of iron sulfidization at the onset of OAE-2 drive regional shifts in pyrite δ34S records - Bryant, RN; Jones, C; Raven, MR; Owens, JD; Fike, DA (eScholarship, University of California, 2020)
Total reduced inorganic S isotope ratios (δ34SCRS) shift toward more negative values across much of the southern North Atlantic just before the onset of the Cenomanian-Turonian Ocean Anoxic Event (OAE-2). At the same time, there is no parallel isotopic change in the significantly larger pool of kerogen (organic) S, which indicates that the distribution and S-isotope composition of sulfide in the environment likely did not drive the change in δ34SCRS. Here, we investigate possible explanations for the negative shift in δ34SCRS values and their divergence from organic S by isolating iron sulfides for morphological identification and grain-specific isotopic analysis using secondary ion mass spectrometry (SIMS). In pre- and syn-OAE-2 sedimentary rocks from Demerara Rise, we find four distinct morphologies of iron sulfides: pyrite framboids (1–20 μm diameter), irregular pyrite aggregates (1–38 μm diameter), large cemented pyrite aggregates (~60 μm diameter), and irregular and cemented aggregates of the pyrite polymorph marcasite (1–45 μm diameter). These different textural groups have distinct S-isotopic compositions that are largely consistent through the onset of OAE-2. As such, the secular change in bulk δ34SCRS values likely reflects the changing proportions of these phases stratigraphically across OAE-2. All textural groups feature resolvable intra-grain δ34S variability, suggesting that the environments in which they formed were characterized by dynamic sulfide δ34S values and/or by partial closed-system distillation. We use grain-specific δ34S distributions to rule out shoaling of the chemocline within the sediments as a mechanism for the observed decrease in δ34SCRS. Instead, we propose that changes in the reactivity of the iron species delivered to Demerara Rise over the ~200 kyr leading up to the onset of OAE-2 impacted the relative contributions of pyrite with S-isotope signatures reflecting the water column, shallow sediments, and deeper sediments to the bulk sedimentary δ34SCRS value. Specifically, the ...